Development of abnormal diagnosis and factory evaluation standards for RV reducer based on vibration characteristics - Xin Wang; Chunlei Li; Suben Lin (Scientific Reports)
Abstract Vibration characteristics are important reference indicators for reflecting the overall performance of RV reducers. At present, there is no factory testing standard for vibration characteristics applicable to production enterprises in the industry. This study conducted vibration characteristic tests on RV40E reducers at different speed ratios. Through a large number of sample comparisons, suitable vibration characteristic factory testing standards for production enterprises were provided. Detailed on-site inspection standards have been developed based on research and analysis results for defective products such as eccentricity, gear defects, and detection errors. This standard can cover 90% of defect types within the factory. The samples are specific and executable. This study solves the problem of the lack of clear vibration detection standards in the industry. For the first time, such a detailed sample set of internal data within a company has been provided. It has extremely practical engineering application value and provides data reference for the development of RV reducer industry.